1963
DOI: 10.1177/11.3.349
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Technique and Hormones on Histochemical Demonstration of Enzymes in Intestinal Epithelium

Abstract: The influence of technical variations and of hypophysectomy and adrenalectomy on the demonstration of enzymes in the jejunal epithelium was studied. The application to fresh frozen sections of procedures for cytochrome c oxidase, succinic dehydrogenase, diphosphopyridine nucleotide diaphorase and lactic dehydrogenase failed to reveal a precise mitochondrial localization, basing the conclusion on comparison with mitochondria as demonstrated by staining of Regaud-fixed mucosa with the Altmann-Masson procedure. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As Nachlas et al (48) have reported, the site of the electron transfer to the tetrazolium salts differs with different tetrazolium compounds. Several recent reports have indicated that interrnediatc electron-carriers such as coenzyme Q10, menadione (vitamin Ks), and PMS can increase the intensity of staining of several dehydrogenases when Nitro-BT or MTT-cobalt are used as final electron-acceptors (9,22,29,(49)(50)(51)(52)(53). It should be emphasized that the enhancement of the staining reaction with intermediate electron carriers, if the same tetrazolium salt is used, depends primarily upon the endogenous diaphorase content of the tissues which are tested.…”
Section: The Role Of Nadi-i-diaphorasementioning
confidence: 99%
“…As Nachlas et al (48) have reported, the site of the electron transfer to the tetrazolium salts differs with different tetrazolium compounds. Several recent reports have indicated that interrnediatc electron-carriers such as coenzyme Q10, menadione (vitamin Ks), and PMS can increase the intensity of staining of several dehydrogenases when Nitro-BT or MTT-cobalt are used as final electron-acceptors (9,22,29,(49)(50)(51)(52)(53). It should be emphasized that the enhancement of the staining reaction with intermediate electron carriers, if the same tetrazolium salt is used, depends primarily upon the endogenous diaphorase content of the tissues which are tested.…”
Section: The Role Of Nadi-i-diaphorasementioning
confidence: 99%
“…No neutral fat could be shown. Taylor and Flaa (1964) also failed to demonstrate neutral fats, but Liu and Baker (1963) found in their investigations a positive stain. These controversial findings may be related to different functional status during the investigations.…”
Section: Resultsmentioning
confidence: 87%
“…A complete review of available information was presented by Patzelt (1936). Various histochemical approaches have been made, but knowledge about the enzymatic content of these cells in the rat is restricted to reports on some enzymes in connexion with other investigations of the small intestine (Lojda and Fabry, 1959;Jervis, 1963;Liu and Baker, 1963). Studies on the heavy metal content of the Paneth cell in rats are frequent and have been carried out more recently by Midorikawa and Eder (1962).…”
mentioning
confidence: 99%
“…In contrast to these reports, Chason and Pearse (1961) observed little enhancement of dehydrogenase activity through the use of PMS and Liu and Baker (1963) encountered artifactual deposition of formaLan when PMS was employed. Hashimoto ~t al.…”
mentioning
confidence: 77%
“…Not explained by this conclusion was the deposition of difarmazan in the tissue in the absence of PMS or in the presence of azide or cyanide. However, a possible explanation for these observations was suggested by the work of Liu and Baker (1963), wherein it was postulated that PMS, because of its affinity for electronegative groups, may form complexes with the tetrazolium salts. This suggested the following explanations for the observations in the present study.…”
Section: Drsct~ss~olimentioning
confidence: 96%